Inhibitory effect of agmatine on naloxone-precipitated abstinence syndrome in morphine dependent rats - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
Effects of agmatine, which is an endogenous polyamine metabolite formed by decarboxylation of L-arginine, were investigated on the morphine abstinence syndrome in rats. Two pellets containing 75 mg morphine base (total 150 mg) were implanted subcutaneously on the back of rats. Seventy-two hours after morphine implantation, agmatine sulphate (20, 30 and 40 mg/kg) or saline was injected intraperitoneally. Forty-five min later, naloxone (2 mg/kg) was injected intraperitoneally to induce precipitated withdrawal. Immediately after naloxone injection, rats were observed for 15 min, and abstinence syndrome signs, which included jumping, wet dog shake, writhing, defecation, ptosis, teeth chattering and diarrhea were counted or rated. Agmatine attenuated all of the signs of the morphine abstinence syndrome dose dependently and significantly. Our results suggest that agmatine prevents naloxone-precipitated abstinence syndrome in morphine dependent rats; thus, this drug may be beneficial in the treatment of opioid dependence.
Keywords: agmatine; nitric oxide; L-arginine; morphine abstinence syndrome; NITRIC-OXIDE SYNTHASE; WITHDRAWAL SYNDROME; L-ARGININE; MICE; MK-801; BRAIN; PHARMACOLOGY; TOLERANCE; CLONIDINE; DRUGS